HUBUNGAN PENGETAHUAN IBU TENTANG ORAL HYGIENE (KEBERSIHAN MULUT) DENGAN TINDAKAN PENANGANAN STOMATITIS PADA BAYI USIA 6-12 BULAN DI KLINIK BERSALIN ELIZA TAHUN 2021 - Eliza Bestari Sinaga; Fifi Ria Ningsih Safari (Universitas Prima Indonesia, 2022)
Stomatitis or oral thrush is an inflammation and ulceration of the mucous membranes of the mouth that often occurs in infancy 6-12 months. The prevalence and distribution of stomatitis in Indonesia is 12%. The occurrence of stomatitis because the mother did not handle it properly. The factor suspected to be the cause is the mother's lack of knowledge. The purpose of this study was to determine the relationship between mother's knowledge about oral hygiene and the treatment of stomatitis in infants aged 6-12 months. This research is a descriptive analytic study with a cross sectional approach. The research was conducted at Eliza Kisaran Maternity Clinic. The research population was 32 people and all of them were used as samples. Data analysis was carried out univariate and bivariate using the Chi Square test at a 95% confidence level ( = 0.05).The results showed that the mother's knowledge about oral hygiene (oral hygiene) was in the sufficient category (38.9%). The treatment for stomatitis in infants was in the good category (52.8%). There is a significant relationship between mother's knowledge about oral hygiene and the treatment of stomatitis in infants at the Eliza Kisaran Maternity Clinic in 2021, p=0.033 <0.05. It is expected that health workers (midwives) will provide counseling to mothers about oral health (oral hygiene) in infants and also about stomatitis in infants, especially mothers who have sufficient and less knowledge so that mother's knowledge becomes good.